1996
DOI: 10.1111/j.1476-5381.1996.tb15166.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cold storage in University of Wisconsin solution on the responses of porcine hepatic arteries to 5‐hydroxytryptamine and bradykinin in vitro

Abstract: 1 Responses to 5-hydroxytryptamine (5-HT), bradykinin and sodium nitroprusside (SNP) were examined in hepatic arteries of the pig 1 h after dissection (fresh) and following 24 h storage in either Ca2+-free Krebs solution or the cryopreservative University of Wisconsin (UW) solution. 2 In fresh arteries contracted to approximately 40% of the maximum response to potassium with U46619, a thromboxane A2-mimetic, concentration-response curves to 5-HT (10-"'-I0-' M) were biphasic, with relaxation at low concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

1997
1997
2002
2002

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…In support of the present study is recent work which demonstrated that cold storage of porcine hepatic arteries led to a loss of endothelial cell function but not smooth muscle function to the spasmogen 5-hydroxytryptamine but not to sodium nitroprusside (Flanders et al 1996). Similarly, another study has demonstrated a progressive reduction in endothelium-dependent relaxation of rabbit aorta following storage of isolated tissue at 4°C (Török et al 1993).…”
Section: Discussionsupporting
confidence: 74%
“…In support of the present study is recent work which demonstrated that cold storage of porcine hepatic arteries led to a loss of endothelial cell function but not smooth muscle function to the spasmogen 5-hydroxytryptamine but not to sodium nitroprusside (Flanders et al 1996). Similarly, another study has demonstrated a progressive reduction in endothelium-dependent relaxation of rabbit aorta following storage of isolated tissue at 4°C (Török et al 1993).…”
Section: Discussionsupporting
confidence: 74%
“…It was also anticipated that preservation in UW solution would not alter the contractile function of donor hepatic arteries. We have shown that the function of rat mesenteric arteries is unaltered after 3 days in a physiological salt solution [19] and UW solution has been shown to preserve the contractile function of porcine [20] and human [18] hepatic arteries. Our results confirmed that the comparison of responses in donor (stored in UW solution) and recipient (removed immediately from the explanted liver) hepatic arteries was valid in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The severity and speed of these changes vary between different cell types with the earliest alterations occurring in nerve fibres and endothelial cells (Kristek et al ., 1993). These morphological alterations are accompanied by functional abnormalities, with endothelium‐dependent relaxation reduced after as little as 24 h storage (Flanders et al ., 1996). Similarly, cryopreservation, which involves storing the tissues in dimethylsulphoxide (DMSO) at either ‐70 or −190°C, produces endothelial cell dysfunction (Ku et al ., 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently the preservative effects of a variety of solutions have been investigated. Whilst this has produced evidence that some preservation solutions (University of Wisconsin, St Thomas’Hospital) are better for preserving endothelial function in rabbit aorta (Eberl et al ., 1993) and porcine hepatic artery (Flanders et al ., 1996), the reasons for these differences are unclear. Indications into the protective action of these solutions are not provided by comparison of their contents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation